La botte piena o la moglie ubriaca?Wine and gender in ancient Rome. - Régis Cavicchioli, Marina (Revista Archai, 2023)
The ways in which each society or group considers alcohol consumption and its effects in multiple cultural contexts is quite different, especially when the discourses refer to this consumption with attention focused on gender. Thus, the associations between the consumption of alcoholic beverages and changes in the sexual behavior of each gender, although present since antiquity, must be understood within the cultural contexts in which they were produced, to understand how each social group deals with certain situations. physiological aspects and from this builds its discourses and interdictions. In this way, a careful return to ancient sources becomes essential, avoiding interpretations based on common sense or tradition, considering the possible differences between normative discourse and everyday practice.